Future feminisms : biolabour, technofeminist care, and transnational strategies - Ferra, Ioanna; Ferra, Fenia; Patelis, Korinna; Karatzogianni, Athina (Digital activism and society: politics, economy and culture in network communication, 2024)
Recent debates regarding abortion law in the US, China, and many EU countries, the rise of far-right politics, and conservatist and extremist movements indicate elevated threats for women rights and the LGBTQ community in a global context. At the same time, '#Metoo' movements were structured through online platform monopolies. In Future Feminisms, female academics from around the globe critically discuss the contemporary postfeminist media culture and bring different stories together to provide opportunities to imagine a connected feminist future. Future Feminisms is an interdisciplinary exploration of the contemporary experiences of women within three different contexts - the private, public, and online spheres. Chapters explore women's experiences of insecurity, instability and change, migration, and diaspora as experienced in both physical and digital communication environments. The diversity of the topics and the thought-provoking chapters are divided into the three sections of 'Gender, Migration, and Decolonization', 'Digital Gender Activism', and 'Motherhood, Home, and Work'. The juxtaposition of how women experience technology, digital media, activism, and feminism is explored through performative practices, including digital, thereby providing an innovative approach in relation to the interplay between political action, the body and artistic works.